A Tale of Four Platforms: Motivations and Uses of Facebook, Twitter, Instagram, and Snapchat Among College Students?. (February 2017) - Alhabash, Saleem; Ma, Mengyan
The current research explores differences between Facebook, Twitter, Instagram, and Snapchat in terms of intensity of use, time spent daily on the platform, and use motivations. The study applies the uses and gratifications (U&G) approach to contrast the four platforms. A cross-sectional survey of college students ( N = 396) asked participants to indicate the intensity of using Facebook, Twitter, Instagram, and Snapchat as well as nine different use motivations. Findings show that participants spent the most time daily on Instagram, followed by Snapchat, Facebook, and Twitter, respectively. They also indicated the highest use intensity for Snapchat and Instagram (nearly equally), followed by Facebook and Twitter, respectively. With regard to use motivations, Snapchat takes the lead in five of the nine motivations. Findings are discussed in relation to the U&G approach and uniqueness of different social media and social networking sites (SNSs).